ALGORITHM OF PATIENT'S TREATMENT WITH THE PRESENCE ANOMALIES OF BITE AND SPEECH DISORDERS - P.S. Flis; N.V. Raschenko; A.O. Melnyk; V.V. Filonenko; A.B. Lopoha (Ukrainian Medical Stomatological Academy, 2018)
Relevance of research. Under complex correction of speech disorders in existing orthodontic pathology, it is important to establish the causative factor, because incorrect tongue articulation, infantile type of swallowing and other bad habits can be the cause of dental and maxillary pathologies and, at the same time, speech disorders. The cause-and-effect relationship between dentoalveolar and speech disorders has been proved. Anomalies and deformations of the dentoalveolar apparatus prevent the sounds from being pronounced normally, contribute to strengthening the habits of improper articulation and complicate logopedic correction. The problem of logopedic correction of sound pronunciation should be addressed comprehensively in collaboration with an orthodontist. The purpose of the research. To treat patients with anomalies of bite and speech disorders according to the proposed algorithm. Materials and methods. To achieve study objectives, 82 patients with severe orthodontic pathology and speech disorders, with normal hearing and intellect, were accepted for treatment. Clinical examination according to the generally accepted scheme, extraoral and intraoral photographs, anthropometry, myography, cephalometry, and logopedic diagnostics of all aspects of speech were conducted. After establishing the diagnosis, determining the treatment plan, orthodontic treatment was performed simultaneously with speech therapy correction. Results and discussion. The first step in the algorithm of successful treatment (correction) of speech disorders and dentoalveolar anomalies was the explanation of its necessity. The second stage of the algorithm was a clinical examination, which included medical history taking and objective methods of examination. The speech therapy part of the algorithm provided for speech therapy diagnosis of all aspects of speech: sound pronunciation, vocabulary, grammar, phonetics. Additional methods of examination were performed for the preparation of the plan, the choice of method and tactics of treatment: extraoral and intraoral photographs, anthropometry, myography, cephalometry, which is an integral part of the second stage of the treatment algorithm for patients with abnormalities and deformations of the dentoalveolar device in conjunction with correction of speech disorders. The third stage of the algorithm was direct orthodontic treatment and speech correction. The retention period is the final stage of the algorithm for treating patients with abnormalities and deformations of the dental apparatus in combination with the correction of speech disorders. Conclusion. The algorithm for treating patients with anomalies of bite and speech disorders consists of the following blocks: motivation, detailed diagnosis, treatment planning and tactics, the active period of orthodontic treatment simultaneously with speech correction and patient management in the retention period.